2005
DOI: 10.1088/1742-6596/9/1/061
|View full text |Cite
|
Sign up to set email alerts
|

Finite volume dependence of hadron properties and lattice QCD

Abstract: Abstract. Because the time needed for a simulation in lattice QCD varies at a rate exceeding the fourth power of the lattice size, it is important to understand how small one can make a lattice without altering the physics beyond recognition. It is common to use a rule of thumb that the pion mass times the lattice size should be greater than (ideally much greater than) four (i.e., mπL ≫ 4). By considering a relatively simple chiral quark model we are led to suggest that a more realistic constraint would be mπ(… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
3
6
0
Order By: Relevance
“…We suspect that this pion mass dependence driving g A away from the experimental value is caused by the finite volume of our calculation. Similar behavior was observed in quenched DWF studies [1,20] and was predicted in a model calculation [50]. However, for pion masses close to our lightest point such a sizable shift is not observed when V is larger than about (2.4 fm) 3 , not only in the quenched case, but also the 2+1 flavor, mixed action calculation in [26] and their updated results [29].…”
Section: A Vector and Axial Chargessupporting
confidence: 90%
“…We suspect that this pion mass dependence driving g A away from the experimental value is caused by the finite volume of our calculation. Similar behavior was observed in quenched DWF studies [1,20] and was predicted in a model calculation [50]. However, for pion masses close to our lightest point such a sizable shift is not observed when V is larger than about (2.4 fm) 3 , not only in the quenched case, but also the 2+1 flavor, mixed action calculation in [26] and their updated results [29].…”
Section: A Vector and Axial Chargessupporting
confidence: 90%
“…Careful studies of the axial charge of the proton by the RBC-UKQCD collaboration [5] have shown a very strong dependence on the size of the lattice used, with the axial charge decreasing rather rapidly at small pion mass (below 0.3-0.4 GeV) as the lattice size goes below 3 fm. Hints of such behaviour had been seen in earlier lattice simulations [6,7,8] and a study of the axial charge for a proton in a finite volume using a chiral bag model did indeed predict results very similar [9] to those found in Ref. [5].…”
Section: Introductionsupporting
confidence: 74%
“…By combining the linear and non-linear boundary conditions, we obtain two eigenvalue equations to be solved for Ω and R The solutions to these equations were shown in Ref. [9], with the pion field, which is of particular interest, growing from the origin to the bag radius and only then starting to decay. For this reason the condition that the lattice volume be large enough to contain the hadron including its pion field is not d ≡ 2L 4m −1 π but rather d ≡ 2L 2R + 4m −1 π .…”
Section: Chiral Bag Modelmentioning
confidence: 99%
“…However, it is difficult to control finite-volume effects (FVE's) in g A , as suggested by quenched calculations [8]. The FVE's have been investigated in effective models [9,10], and also in heavy baryon chiral perturbation theory (HBChPT) [11][12][13]. The FVE's in HBChPT are inconsistent with lattice calculations unless contributions of the baryon resonance are included.…”
mentioning
confidence: 99%